Research on the Energy Management Strategy for Mine Electric-wheel Dump Truck with Hybrid Power System - CHEN Lingjian; TANG Xunlu; HE Chengzhao; LIU Huirong; YAN Xiaoyu (Kongzhi Yu Xinxi Jishu)
Traditional mine dump truck using diesel-electric drive technology have high energy consumption and serious pollution. To improve fuel economy of a hybrid power dump truck, firstly, it analyzes system composition, working mode and transportation condition characteristics of the hybrid power electric-wheel mining dump truck. Secondly, according to the mine driving conditions of the electric-wheel dump truck, an energy management strategy based on the driving pattern recognition is proposed according to the driver's intention and the vehicle state. Finally,to minimize the instantaneous equivalent fuel consumption of the whole hybrid power system, the equivalent consumption minimization strategy is used to optimize the instantaneous power distribution between the engine and battery. In order to verify the proposed energy management strategy, on site mining road test is conducted. Test results show that the fuel consumption of the hybrid power electric-wheel dump truck is 45.52 L/trip, which is 10.2% lower than that of the electric-wheel dump truck with full diesel engine mode.